Optimum Firm Location and the Theory of Production - David L. Emerson (Queen's University, Department of Economics, 1972)
Theories of firm location have, over the last century, fallen into two basic streams, location in homogeneous space and location in heterogeneous space. The former stream normally builds on the notion that consumers or demanders of a firm's product are evenly distributed over geographic space, so that demand considerations become intrinsically enmeshed with market area considerations. Location in heterogenous space incorporates the notion that c.i.f. prices faced by the locator vary continuously over space, either because inputs and outputs must be transported at positive cost or because market determined values for the rights to alternative locations are not identical. The emphasis in this paper will be on locational problems of the latter sort.
Keywords: 330